The Duration Of Hormonal Contraceptive Use Is Not Related To Weight Gain - Lely firrahmawati; Endang Sri Wahyuni; Ika Silvitasari (P3M Universitas 'Aisyiyah Surakarta, 2022)
Hormonal contraceptives, especially injectable and oral contraceptives, are most widely used by the community, this is because they are easy and affordable to use. The purpose of this study was to determine the difference between the duration of hormonal contraceptive use and weight gain in hormonal family planning (KB) acceptors. This study uses observational analytic with a cross-sectional approach. The population of this study were all hormonal family planning acceptors in Sidoarjo District, Sragen Regency who met the inclusion and exclusion criteria. The number of samples in this study were 32 respondents who were taken using a consecutive sampling technique. The statistical test used in this study is the Independent T test. The results showed that the average use of hormonal contraception was 86.1 (52.10) months. most of the respondents did not experience an increase in body weight 81.3%,. The results of the statistical test showed a p value of 0.908, which means that there was no difference in the duration of the use of hormonal contraception for family planning acceptors with weight gain.